2020
DOI: 10.1371/journal.pone.0243637
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping in the digital age: Male language is “ingenious”, female language is “beautiful” – and popular

Abstract: The huge power for social influence of digital media may come with the risk of intensifying common societal biases, such as gender and age stereotypes. Speaker’s gender and age also behaviorally manifest in language use, and language may be a powerful tool to shape impact. The present study took the example of TED, a highly successful knowledge dissemination platform, to study online influence. Our goal was to investigate how gender- and age-linked language styles–beyond chronological age and identified gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 81 publications
(162 reference statements)
0
18
0
Order By: Relevance
“…Writing that scores high on this measure is often "cold," "dispassionate," or impersonal compared to writing that scores low on this measure (Seraj et al, 2021). Analytic thinking is an important marker of various psychological processes and individual differences, including persuasion (Markowitz, 2019(Markowitz, , 2020, cultural trends in politics (Jordan et al, 2019), and gender in entertainment speeches (Meier et al, 2020). Prior work has also used analytic thinking to indicate how members of the World Health Organization appraised rising COVID-19 cases and deaths over time (Markowitz, 2021).…”
Section: Psychological Trauma and Emotional Upheaval As Revealed In Academic Writingmentioning
confidence: 99%
“…Writing that scores high on this measure is often "cold," "dispassionate," or impersonal compared to writing that scores low on this measure (Seraj et al, 2021). Analytic thinking is an important marker of various psychological processes and individual differences, including persuasion (Markowitz, 2019(Markowitz, , 2020, cultural trends in politics (Jordan et al, 2019), and gender in entertainment speeches (Meier et al, 2020). Prior work has also used analytic thinking to indicate how members of the World Health Organization appraised rising COVID-19 cases and deaths over time (Markowitz, 2021).…”
Section: Psychological Trauma and Emotional Upheaval As Revealed In Academic Writingmentioning
confidence: 99%
“…Clearly, media reports are not correct for frontline nurses, who are expected to demonstrate professional medical skills during their frontline experiences rather than rely on their appearance and identities to be considered heroes of the moment. Such stereotyped female power roles are the embodiment of the ideology of patriarchal society [ 39 ]. The media tends to commoditize this gendered power, but in fact, women need to be seen as individuals who can speak and be heard.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, if they encounter a female scientist who is using complex language, this might violate their expectations and lead to evaluating the message unfavorably. Meier et al (2020) found some support for this hypothesis when they evaluated the language used by males and females who have given a TED Talk. Specifically, females who embraced female communication stereotypes by exuding warmth and using a narrative style for scientific explanations received higher ratings on recorded talks than females who used a more analytically, stereotypical male style.…”
Section: Literature Reviewmentioning
confidence: 99%